Studi In Silico: Potensi Senyawa Spesifik Kulit Batang Faloak (Sterculia quadrifida R. Br) sebagai Anti-Helmintik - Riwu, Audrey Gracelia; Riwu, Katty Hendriana Priscilia; Pua Upa, Nurul Fatmawati; Kale, Maria Laurenci Fanny Permata; Jannah, Insani Fitrahulil; Wuhan, Yustinus Oswin Primajuni (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2025)
Helminthiasis remains a significant global public health issue, particularly in tropical and subtropical regions. The extensive and repeated use of synthetic anthelmintic agents, including albendazole and mebendazole, has contributed to the emergence of drug resistance among various parasitic species. Therefore, the exploration of plant-derived compounds with potential anthelmintic activity is urgently needed. This study investigated the potential of bioactive compounds from the stem bark of Faloak (Sterculia quadrifida R. Br) as inhibitors of the Mitochondrial Rhodoquinol-Fumarate Reductase (MRFR) protein through an in silico approach. Five compounds: epicatechin, d-catechin, catechin-(4α→8)-catechin, spinasterol, and spinasterone were analyzed, with Atpeni as the control. Drug-likeness evaluation was conducted using Lipinski’s Rule of Five, while molecular docking, visualization and molecular interaction analysis was performed using PyRx, PyMOL, and Discovery Studio. Four compounds satisfied Lipinski’s criteria, indicating favorable pharmacokinetic properties. Among them, spinasterol and spinasterone demonstrated the strongest binding affinities to MRFR (–10.1 and –9.2 kcal/mol, respectively), exceeding that of the control ligand (–6.4 kcal/mol). Hydrophobic interactions involving key residues such as Leu146, Ala149, and Val153 contributed to complex stability. These results suggest that Faloak stem bark contains promising bioactive compounds that may serve as natural anti-helmintic candidates, warranting further in vitro and in vivo validation